8(6x-7)=96x

Simple and best practice solution for 8(6x-7)=96x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(6x-7)=96x equation:


Simplifying
8(6x + -7) = 96x

Reorder the terms:
8(-7 + 6x) = 96x
(-7 * 8 + 6x * 8) = 96x
(-56 + 48x) = 96x

Solving
-56 + 48x = 96x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-96x' to each side of the equation.
-56 + 48x + -96x = 96x + -96x

Combine like terms: 48x + -96x = -48x
-56 + -48x = 96x + -96x

Combine like terms: 96x + -96x = 0
-56 + -48x = 0

Add '56' to each side of the equation.
-56 + 56 + -48x = 0 + 56

Combine like terms: -56 + 56 = 0
0 + -48x = 0 + 56
-48x = 0 + 56

Combine like terms: 0 + 56 = 56
-48x = 56

Divide each side by '-48'.
x = -1.166666667

Simplifying
x = -1.166666667

See similar equations:

| -1/4(12x+4)+1/7(49x+21) | | 8-7x=119-28x | | 2x+3=x+85 | | -x^2+17x-23=5x+9 | | x^4-4x^2-2=0 | | 1.16y=y+1+0.5 | | 50-7x=20x+20 | | 5x+4=28x+12 | | 1.16y=y+1+0.3 | | 1.2=2x/3+5.1 | | 1.16y=y+1+1 | | x/5+8=6 | | -x^2+2x+58=-x+4 | | x/5+12=-20 | | 5x/2=11+2x/3 | | 3x^2y-6xy^2= | | 6x+13=69-3x | | 1/3(5-3x)=5/6(x-2) | | x-39=79 | | 6(3x-12)=54x | | 13x+12=5x+10 | | 5m+20=6m+12 | | -3(x-2.7)=1.8 | | 5y^2-17y+14= | | -5x^2-5x+10=-2x^2-4x+7 | | 7(x-3)=-4x+89 | | 8.4=-6(a+2.4) | | -3x^2-11x+5=-4x+6 | | 236-6x=39x+16 | | 5m=-2+3m | | m/6-1.5=-7 | | 6x+20=38 |

Equations solver categories